Physicochemical properties of magnetically enhanced shape memory polymer composites doped with NiMnGa - Pekdemir, Mustafa Ersin; Kaya, Mustafa; Coskun, Mustafa; Aydogdu, Yildirim; Kok, Mediha; Kuzu, Serpil Yalcin (Springer, 2023)
In recent years, there has been a significant demand for shape memory materials due to their smart characteristics. NiMnGa has special interest because of its magnetic shape memory features which can be used in actuators, sensors, dampers, and energy harvesting. The production of NiMnGa has a substantial cost resulting in usage of a shape memory polymer composite with the alloy which brings advantages such as size, and shape structure. For this purpose, a new multifunctional smart material was studied by combining Poly lactic acid (PLA)/Poly ethylene glycol (PEG) blend obtained with Ni49.5Mn29.5Ga21 (in % atomic). Different ratios of the alloy were doped into the blend to investigate the effect of the alloy on the characteristic features of the composite. Physicochemical properties of NiMnGa enriched composites were analyzed by attenuated total reflectance infrared spectroscopy (ATR-IR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). From DSC analysis it is concluded that the magnetically enhanced PLA/PEG films with the alloy had two important phase transformations. Although NiMnGa shape memory alloy did not affect the initial decomposition temperature (T-i) of the PLA/PEG blend much, the residue ratio increased with increasing alloy content. The characteristic XRD signal of the alloy becomes observable with the increasing amount of NiMnGa in the composite. In addition, the diamagnetic PLA/PEG blend gained magnetic properties with addition of the alloy. It is also observed that NiMnGa had a positive effect on the shape memory feature of the polymer blend.
Keywords: Shape memory polymers; Ni-Mn-Ga; Polylactic acid; Polyethylene glycol; Composite; Magnetically sensitive